Formation of leaf surface under the influence of soybean inoculation and feed - Джемесюк, О. В.; Каленська, С. М.; Новицька, Н. В. (Scientific Progress & Innovations, 2016)
The effects of inoculation seed, top dressing fertilizers, and multi-chelate complex of colloidal solution of metal nanoparticles on a background of mineral fertilizers on the dynamics of the formation of leaf surface of sowing soybean varieties are presented. Field research was conducted in typical black soil of Forest-Steppe zone of Ukraine at the Department of Plant in separate unit of the National University of Life and Environmental Sciences of Ukraine «Agronomic Research Station». Options for research include inoculation of seed by bacterial drug «HayKot Super» + «HayKot Super Extender», sustained by budding complex fertilizers «VuksalKombi Plus» (2 l/ha) and «Sprout Bean» (2 l/ha), and patented royal colloidal solution complex (Fe, Mn, Mo, Co, Cu, Zn, Ag) nanoparticles of metals (240 mg/1 l/ha). We established that the largest area of ​​leaves found in ultraearly sort «Legend» and early ripening varieties «Horol» which in the variant with seed inoculation was 23,0 and 27,7 thousand m2/ha corresponding figure of 22,8 and 25,5 thousand m2/ha in the version without inoculation. The use of complex metal nanoparticles at a concentration of 240 mg/l for spraying soybeans in early budding increases leaf area at flowering stage to 22,9 for ultraearly and 28,1 thousand m2/ha – for early ripening varieties of soy. Maximum leaf surface in the experiment: 24,4 thousand m2/ha for sort «Legend» and 30,9 thousand m2/ha – for sort «Horol» formed by the combination of seed inoculation «HayKot Super» + «HayKot Super Extender», and foliar feeding complex micronutrients «Sprout Bean».